Pengaruh Tingkat Pendapatan Petani Karet terhadap kesejahteraan - Rika Rahmadina Putri,S.E.I., M.Si; Mudzakir Ilyas; Alif Pratama Ridhoillah (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
This research aims to determine the effect of rubber farmers' income on family welfare in the Tanjung Rambang sub-district, Rambang Kapak Tengah sub-district, Prabumulih City. The method used in this research is a quantitative method using a sample of 76 respondents. Sampling used the Quota Sampling technique. The data analysis method used in this research is simple linear regression to see how much influence rubber farmers' income has on family welfare in the Tanjung Rambang sub-district, Rambang Kapak Tengah District, Prabumulih City. Based on the results of the simple linear regression analysis that was carried out in this research. Judging from the results of the t test that has been carried out, tcount 20.155 > ttable 1.665, so H0 can be rejected and Ha accepted, it can be concluded that the income of rubber farmers has a positive effect on family welfare in the Tanjung Rambang sub-district, Rambang Kapak Tengah District, Prabumulih City.